Long Term Effect of Yakson Stimulation on Neurobehavior and Weight Gain in Preterm Infants: A Pilot Study. - Vaniya, Jigisha; Muley, Prasad; Gadhavi, Bhavana (Journal of Neonatal Surgery, 2025)
Background: Preterm and term neonates need specialized treatment to ensure ideal growth and neurodevelopment. Non-pharmacologic interventions, such as Yakson stimulation, have been investigated for improving weight gain and neurobehavioral development. Yet, evidence of long-term studies evaluating sustained effects on neonatal development remains limited. Introduction: Yakson stimulation, a traditional Korean therapeutic touch technique, has been reported earlier to be related to enhanced physiological and behavioral outcomes in neonates. In this study, the long-term impact of Yakson stimulation on weight gain and neurobehavioral development in preterm and term neonates is being assessed, insights into which are anticipated in terms of its effectiveness as a supportive neonatal care intervention. Methodology: Randomized controlled trial (RCT) was performed involving preterm and term neonates who were given Yakson stimulation for a set period. The control group was given regular neonatal care without Yakson stimulation. Weight gain, neurobehavioral testing, and developmental milestones were measured at several follow-up intervals. Discussion: Results show that Yakson stimulation is associated with substantial weight gain and better neurobehavioral results in neonates. The results are in agreement with previous short-term trials, and it emphasizes the potential of Yakson stimulation in neonatal care. The trial also suggests possible mechanisms, including improved circulation, reduced stress, and enhanced parent-infant attachment. Conclusion: Yakson stimulation appears to be an effective non-pharmacologic strategy in enhancing neonatal growth and neurodevelopment. Long-term follow-up trials would be necessary to further establish its efficacy and to examine its integration into routine neonatal care.